Revisioning christology : theology in the reformed tradition - Crisp, Oliver (England, Ashgate, 2011)
This book offers a series of studies in the Christology of key representatives in the Reformed tradition engaging their thought for contemporary dogmatics. --from publisher description
Donald Baillie (1887-1954), paradox and christology -- John Calvin (1509-1564) on the motivation for the incarnation -- Jonathan Edwards (1703-1758), idealism and christology -- William Shedd (1820-1894) on the theanthropic person of Christ -- John Owen (1616-1683) on spirit christology -- Kathryn Tanner (1954- ) on incarnation as atonement
Includes bibliographical references and index
Keywords: Jesus Christ -- History of doctrines; Reformed Church -- Doctrines